Comparison and optimization of ten phage encoded serine integrases for genome engineering in Saccharomyces cerevisiae - Xu, Zhengyao; Brown, William (BioMec Central, 2016)
Background: Phage-encoded serine integrases, such as ϕC31 integrase, are widely used for genome engineering but have not been optimized for use in Saccharomyces cerevisiae although this organism is a widely used organism in biotechnology.